Statistik Deskriptif - Lenni Masnidar Nasution (Sekolah Tinggi Agama Islam Sumatera Medan, 2017)
Descriptive statistics are part of the statistical data collection, presentation, determination of the values of statistics, charting or drawing about something. The type of statistical techniques used to test the hypothesis of descriptive must match the type of data or variable based on the measurement scale, ie nominal, ordinal, or interval / ratio.